2015
DOI: 10.1002/elan.201400644
|View full text |Cite
|
Sign up to set email alerts
|

Lysine, Arginine, and Histidine Residues in Peptide‐Catalyzed Hydrogen Evolution at Mercury Electrodes

Abstract: Dedicated to Professor R. G. Compton on the Occasion of his 60 th Birthday 1IntroductionNucleic acids are electroactive species undergoing reduction and oxidation of their base residues at various types of electrodes.E lectrochemistry of nucleic acids embraces aw ide variety of natural and synthetic molecules including DNAand RNA [1][2][3].Incontrast, electrochemistry of proteins was concentrated mostly on the fast reversible electrode processes of non-protein redox centers in conjugated proteins [4][5][6][7][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In the last decade, it has been found that amino acids (AA) containing labile protons such as cysteine, lysine, arginine, and histidine can be involved in CHER of peptides , polyamino acids and proteins themselves at neutral pH. Specifically, the proton‐exchangeable groups for individual AA are imidazolium (His), ϵ‐ammonium (Lys), guanidinium (Arg) and thiol group (Cys). His residues, at neutral pH, behaved as a weaker catalyst for CHER (considering pKa values) in comparison to Arg and Lys residues .…”
Section: Comparison Of Individual Amino Acid (Aa) Content In Selectedmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, it has been found that amino acids (AA) containing labile protons such as cysteine, lysine, arginine, and histidine can be involved in CHER of peptides , polyamino acids and proteins themselves at neutral pH. Specifically, the proton‐exchangeable groups for individual AA are imidazolium (His), ϵ‐ammonium (Lys), guanidinium (Arg) and thiol group (Cys). His residues, at neutral pH, behaved as a weaker catalyst for CHER (considering pKa values) in comparison to Arg and Lys residues .…”
Section: Comparison Of Individual Amino Acid (Aa) Content In Selectedmentioning
confidence: 99%
“…Specifically, the proton‐exchangeable groups for individual AA are imidazolium (His), ϵ‐ammonium (Lys), guanidinium (Arg) and thiol group (Cys). His residues, at neutral pH, behaved as a weaker catalyst for CHER (considering pKa values) in comparison to Arg and Lys residues . Cys participation in CHER was studied in earlier works dealing with the peak H .…”
Section: Comparison Of Individual Amino Acid (Aa) Content In Selectedmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this accumulated knowledge it is not surprising that the Cys‐p53 aptamer exhibits a good catalytic activity towards the hydrogen evolution at the mercury electrode. Indeed, around the physiological pH, the amino acid residues which are the most active for the catalytic hydrogen evolution reaction are Cys, Lys, and Arg , the aptamer containing the former two. In addition, the peptide must be present at the electrode at the potential (and at the moment) at which the catalysis takes place.…”
Section: Resultsmentioning
confidence: 99%
“…This method represents a rapid analysis of the nanomolar concentrations of particularly all proteins without any additional labelling or modification . The CPS signal of a protein was denominated as “peak H” and its appearing in the protein analysis is a result of catalytic hydrogen evolution reaction (CHER) of amino acids residues bearing exchangeable proton, such as Cys, Arg, Lys, and His . Global and local changes in the protein structure such as denaturation , mutation , chemical modification , damage , redox state , and aggregation can be studied using CPS due to susceptibility of proteins to effects of electric field.…”
Section: Introductionmentioning
confidence: 99%